Legality of UMKM based establishment of startup by students of State Polytechnics of Semarang - Irawan - Malebra; Nur - Rini; Paniya - Paniya; Umar - Farouk; Erika - Devie (Admisi dan Bisnis, 2021)
According to Presidential Regulation No. 98/2014 on Licensing for micro and small businesses, micro and small entrepreneurs are required to register business legality. However, the implementation effectiveness of this regulation is still unknown. This study aims to analyze the profiles of Semarang State Polytechnic (Polines) students who have a business and the legality constraints of MSME startups. This research uses empirical juridical method. The data was collected through an online questionnaire using the Surveymonkey application for Polines students who have a startup business based on MSMEs. There are 139 students who have businesses participating in this survey. More than half of their businesses are in the form of MSMEs. A third are engaged in the culinary and creative industries. 78.26% use digital technology platforms. Almost all of them use the Instragam platform and some use the Facebook, Shopee, Bukalapak, twitter, YouTube, Tokopedia platforms. As much as 82.86% stated that they do not have legality by law. Even though they think that business legality is important, they have not tried to register because of several factors such as being busy. Some stated that they intend to register their business when it runs smoothly, has the potential to become large, and has costs. Their startup business has not been registered because they feel that their business is already running smoothly. It can be concluded that the implementation of business legality regulations is still low and implies the need for synergy between local governments, lecturers, and practitioners to jointly socialize and assist business legality